Primary School Teachers’ Understanding of Critical Thinking in KSSR Classroom and Its Importance to Students - Kamarulzaman, Wirawani; Hashim, Rosnani (International Journal of Engineering and Technology, 2018)
Critical thinking is one of the 21st century skills that should be equipped to students to prepare them with the challenges ahead. Teachers should be prepared to teach them these skills and their understanding of the concept itself should be explored. Thus, the objectives of the study are to investigate teachers’ understanding of critical thinking in KSSR (Kurikulum Baru Sekolah Rendah: New Primary School Curriculum) classroom and to explore their perception on the importance of the skills to student. Six primary school teachers were interviewed and transcriptions were made. The data was analyzed through colour coding and themes were emerged from the analysis. The findings found that teachers view critical thinking as the ability to gather information, express thoughts, solve problems and analyze. They were found the skills are important for students as it helps them apply knowledge and make decisions. It is hoped that in future research, the definition of critical thinking could be collected quantitatively from teachers. The study will be benefited to teachers to improve teaching method by understanding the concept itself.